The Malmedy Massacre : the war crimes trial controversy - Remy, Steven P. (Harvard University Press, 2017)
Introduction: an American courtroom in Dachau -- The commitments of a bad reputation: terror war in the Ardennes -- Now it comes home to us: creating the "Malmedy Massacre" -- Like a division reunion: launching the investigation -- The psychological approach: American interrogators -- Nazi method boys: the first torture allegations -- A monstrous slaughter machine: the prosecution's case -- Entirely a heat of battle case: the defense -- Other battlefields: Willis Everett and the amnesty campaign -- The sword of public opinion: the torture stories in the U.S. -- The daring fists of Lieutenant Perl: tales of torture in Schwaebisch Hall -- Avenging angels: German clergy and the massacre -- Lie detectors: interrogating American interrogators -- Red jackets: releasing the prisoners